(untitled) (Journal of Parents and Teachers, 2025)
The story is set in the summer of 1984 and follows Rita, a seven-year-old girl living in Seville with her parents and her five-year-old brother, Lolo. Her greatest dream is to spend the summer holidays at the beach—a desire so strong that it becomes the center of her interactions and fantasies. The narrative also explores aspects of her school life and leisure time in the neighborhood, with Lolo as her closest confidant and partner in adventures, sharing a special bond of love and complicity. Within the family, however, a tense atmosphere prevails, marked by her father’s authoritarianism and frequent arguments. From a child’s perspective and with subtlety, the film reveals clear signs of violence and its impact on family relationships. Amid everyday life, the longing for a summer trip, and her unique connection with her brother, Rita experiences a vacation that becomes a turning point in her life.